Annular erythema in primary Sjögren's syndrome: description of 43 non-Asian cases. (February 2014) - Brito-Zerón, P; Retamozo, S; Akasbi, M; Gandía, M; Perez-De-Lis, M; Soto-Cardenas, M-J; Diaz-Lagares, C; Kostov, B; Bove, A; Bosch, X; Perez-Alvarez, R; Siso, A; et al.
Objective: The objective of this paper is to evaluate the prevalence and characterize the main epidemiological, clinical and immunological features of annular erythema (AE) in non-Asian patients with primary Sjögren's syndrome (SS). Methods: We carried out a retrospective study searching for AE in 377 Spanish patients with primary SS fulfilling the 2002 American-European criteria. In addition, we searched PubMed (1994–2012) using the MeSH terms "annular erythema" and "primary Sjögren's syndrome" for additional cases. All cases with AE reported in patients with SS associated with systemic lupus erythematosus were excluded. Results: In our Spanish cohort, we found 35 (9%) patients diagnosed with AE. All were white females, with a mean age of 47 years at diagnosis of AE. AE preceded diagnosis of SS in 27 (77%) patients. Cutaneous AE lesions involved principally the face and upper extremities. All patients reported photosensitivity, with cutaneous flares being reported during the warmest months in 93% of patients. Immunological markers consisted of anti-Ro/La antibodies in 31 (89%) patients. In the literature search, we identified eight additional non-Asian patients with primary SS diagnosed with AE. In comparison with 52 Asian patients, the 43 non-Asian patients with AE related to primary SS were more frequently women (100% vs 78%, p  = 0.008), and cutaneous lesions were less frequently reported in the face (55% vs 81%, p  = 0.045) and more frequently in the neck (40% vs 14%, p  = 0.041). Immunologically, non-Asian patients had a lower frequency of anti-Ro antibodies and a higher frequency of negative Ro/La antibodies, although the differences were not statistically significant. Conclusion: AE is not an exclusive cutaneous feature of Asian patients with primary SS. In addition to the characteristic cutaneous expression, AE has a very specific clinical and immunological profile: often presenting before the fulfillment of SS criteria, overwhelmingly associated with anti-Ro antibodies but weakly associated with other immunological markers and the main systemic SS-related features.